Use of Moringa oleifera Flower Pod Extract as Natural Preservative and Development of SCAR Marker for Its DNA Based Identification. (4th July 2016) - Gull, Iram; Javed, Attia; Aslam, Muhammad Shahbaz; Mushtaq, Roohi; Athar, Muhammad Amin
Abstract : The use of Moringa oleifera as natural food preservative has been evaluated in the present study. In addition, for quality assurance, the study has also been focused on the shelf life of product to authenticate the identification of plant by development of DNA based marker. Among the different extracts prepared from flower pods of Moringa oleifera, methanol and aqueous extract exhibited high antibacterial and antioxidant activity, respectively. The high phenolic contents (53.5 ± 0.169 mg GAE/g) and flavonoid contents (10.9 ± 0.094 mg QE/g) were also recorded in methanol and aqueous extract, respectively. Due to instability of bioactive compounds in aqueous extract, methanol extract is considered as potent natural preservative. The shelf life of methanol extract was observed for two months at 4°C under dark conditions. The developed SCAR primers (MOF217/317 /MOR317 ) specifically amplified a fragment of 317 bp from DNA of Moringa oleifera samples collected from different regions of Punjab province of Pakistan. The methanol extract of Moringa oleifera flower pods has great potential to be used as natural preservative and nutraceutical in food industry.